Study of the Acute Toxicity of a New Dosage Form of Naloxone Hydrochloride for Intranasal Administration - Bariev, Eduard A.; Krasnyuk, Ivan I.; Anurova, Maria N.; Bakhrushina, Elena O.; Smirnov, Valery V.; Bardakov, Alexander I.; Demina, Natalya B.; Krasnyuk, Ivan I., Jr. (Drug Research, 2020)
The experiment was conducted on 10 Wistar rats, male and female, with initial body weight 270–280 g (males) and 250–260 g (females). The drug was administered using a spray cap in 10 doses of 0.1 mg at 45 min intervals. The average cumulative dose of the drug per naloxone hydrochloride was 36.6 mg/kg for males and 39.4 mg/kg for females. The animals were monitored for 2 weeks after the exposure and then euthanized by a gentle decapitation.We noticed that after each drug administration the animals showed a decrease in motor activity. During the observation period there were no animal deaths or signs of abnormalities in their general state or behavior. Beginning on day 7 a significant increase in body weight of the animals was noted in comparison with the initial data. The relative mass of the internal organs of the treated rats remained within the physiological norm.We conclude that naloxone hydrochloride after an intranasal administration at 36.6 mg/kg for males and 39.4 mg/kg for females does not cause death of animals and or have a toxic effect on their general state, does not change their protein metabolism characteristics or the appearance of the internal organs and their mass.
Keywords: pharmaceutics; toxicology; pharmacology; drug research